Rebamipide increases barrier function and attenuates TNFα-induced barrier disruption and cytokine expression in human corneal epithelial cells. Issue 7 (20th April 2013) - Tanaka, Hiroshi; Fukuda, Ken; Ishida, Waka; Harada, Yosuke; Sumi, Tamaki; Fukushima, Atsuki
Abstract : Background: Disruption of corneal epithelial barrier function by inflammation may contribute to the development of dry eye. The effects of rebamipide, a drug used for the treatment of dry eye, on barrier function and cytokine expression in a human corneal epithelial (HCE) cell line were examined. Methods: Barrier function of HCE cells was evaluated by measurement of transepithelial electrical resistance (TER). The subcellular localisation of the tight junction protein zonula occludens (ZO)-1 was examined by immunofluorescence analysis. The release of cytokines was determined with ELISAs, and the intracellular abundance of cytokine mRNAs was quantitated by reverse transcription and real-time PCR analysis. Degradation of the nuclear factor-κB inhibitor IκBα was detected by immunoblot analysis. Results: Rebamipide increased TER of HCE cells in a concentration-dependent manner as well as attenuating the loss of TER and the disappearance of ZO-1 from the cell surface induced by tumour necrosis factor α (TNFα). Rebamipide also suppressed TNFα-induced expression of interleukin-6 and interleukin-8 at the mRNA and protein levels and inhibited the TNFα-induced degradation of IκBα. Conclusions: The upregulation of barrier function and the anti-inflammatory effects of rebamipide, together with its mucin secretagogue activity, may contribute to the effectiveness of this drug for the treatment of dry eye.